Fecal calprotectin level correlated with both endoscopic severity and disease extent in ulcerative colitis. Issue 1 (December 2016) - Kawashima, Kousaku; Ishihara, Shunji; Yuki, Takafumi; Fukuba, Nobuhiko; Oshima, Naoki; Kazumori, Hideaki; Sonoyama, Hiroki; Yamashita, Noritsugu; Tada, Yasumasa; Kusunoki, Ryusaku; Oka, Akihiko; Mishima, Yoshiyuki; et al.
Abstract Background The relationship between fecal calprotectin (FC) and disease extent in ulcerative colitis (UC) has not been fully elucidated. The aim of this study was to clarify the correlation of FC with disease extent and severity in UC patients. Methods UC patients scheduled to undergo an ileocolonoscopy were enrolled and fecal samples for FC measurement were collected prior to the procedure. A Mayo endoscopic subscore (MES) was determined for each of 5 colonic segments. To evaluate the association of FC with extent of affected mucosa as well as disease severity, we assessed the correlation of FC level with the sum of MES (S-MES) for the 5 colonic segments as compared to the maximum score of MES (M-MES). Results FC measurements in conjunction with findings from 136 complete colonoscopies in 102 UC patients were evaluated. FC level showed a stronger correlation with S-MES (correlation coefficientr  = 0.86, p  < 0.001) as compared to M-MES (r  = 0.79, p  < 0.001). In patients with an M-MES of 1, 2, and 3, FC level showed a significant correlation with S-MES (r  = 0.67, p  < 0.001;r  = 0.70, p  < 0.001;r  = 0.47, p  = 0.04, respectively). Our findings indicate that FC level is elevated in patients with greater areas of affected mucosa even in those with the same M-MES value. Conclusions FC level was shown to be correlated with the extent of affected mucosa as well as severity in UC patients, thus it is useful for precise assessment of mucosal inflammation.